Educational Policy of Comprehensive School: Outlining the Conceptual Space - Bartaševičius, Robertas; Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2012)
The aim of the article is to outline the conceptual space of education policy of a comprehensive school. The article deals with the usage of the definitions “policy”, “politics” and “polity” and their influence on the definition of “educational policy”. Efforts are being made to distinguish relations between the definitions “public policy” and “educational policy” provided in scientific literature. The authors state that educational policy should be analyzed on several levels: national, regional, local or a particular educational institution’s, e.g., school. The authors conclude that the educational policy of a school has to be considered as a whole of all purposeful actions aimed at the implementation of the strategic goals of a school. This is an activity with the contents comprising the values, priorities, goals and decisions as well as the measures of their implementation. The educational policy of a school is strongly influenced by the context. The most important role in the formulation and implementation of educational policy at a school level belongs to its leader / executive officer whose activities are oriented towards the strategic (and not tactical or administrational) level.